2019
DOI: 10.5194/se-2019-32
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lithosphere tearing along STEP faults and synkinematic formation of lherzolite and wehrlite in the shallow subcontinental mantle

Abstract: Abstract. Subduction-Transform Edge Propagator (STEP) faults are the locus of continual lithospheric tearing at slab edges, resulting in sharp changes in the lithospheric and crustal thickness and triggering lateral and/or near-vertical mantle flow. However, the mechanisms at the lithospheric mantle scale are still poorly understood. Here, we present the microstructural study of olivine-rich lherzolite, harzburgite and wehrlite mantle xenoliths from the Oran volcanic field (Tell Atlas, NW Algeria). This alkali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 109 publications
2
20
0
Order By: Relevance
“…Recent studies of the westernmost Algerian margin (Badji et al, 2015), the Betics and the Rif (Garcia-Castellanos and Villaseñor, 2011;de Lis Mancilla et al, 2015 have shown that the structure of the southern and northern margins of the Balearic and Alboran basins is characterized by an abrupt transition between continental and oceanic domains, in agreement with a STEP (Subduction-Transform-Edge-Propagator) fault origin (Govers and Wortel, 2005). This slab tear propagation is therefore assumed to have induced, from 16 to 8 Ma, the opening of the central and western Algerian basin along a left-lateral sub-vertical fault, thus forming a transform-type margin (Medaouri, 2014;Medaouri et al, 2014;van Hinsbergen et al, 2014;Hidas et al, 2019).…”
Section: Geodynamic and Seismotectonic Settingsmentioning
confidence: 90%
“…Recent studies of the westernmost Algerian margin (Badji et al, 2015), the Betics and the Rif (Garcia-Castellanos and Villaseñor, 2011;de Lis Mancilla et al, 2015 have shown that the structure of the southern and northern margins of the Balearic and Alboran basins is characterized by an abrupt transition between continental and oceanic domains, in agreement with a STEP (Subduction-Transform-Edge-Propagator) fault origin (Govers and Wortel, 2005). This slab tear propagation is therefore assumed to have induced, from 16 to 8 Ma, the opening of the central and western Algerian basin along a left-lateral sub-vertical fault, thus forming a transform-type margin (Medaouri, 2014;Medaouri et al, 2014;van Hinsbergen et al, 2014;Hidas et al, 2019).…”
Section: Geodynamic and Seismotectonic Settingsmentioning
confidence: 90%
“…Under the central Betics to the north and under Morocco to the south, a sharp lithospheric and crustal step can be recognized in the receiver function computations, tomographic images, and gravimetric data (e.g., Spakman & Wortel, 2004; Bezada et al, 2013; Levander et al, 2014; Mancilla et al, 2015; Petit et al, 2015; Diaz et al, 2016; Molina‐Aguilera et al, 2019) In northern Morocco in particular, a sharp change in crustal thickness is visible at the city of Al Hoceima, where the crust is more than 40 km thick to the west but less than 30 km thick to the east (Diaz et al, 2016). These abrupt offsets are interpreted as the termination of the Iberian and Nubia lithosphere caused by a vertical STEP fault (e.g., Spakman & Wortel, 2004; Levander et al, 2014; Mancilla et al, 2018; Hidas et al, 2019). These lithospheric STEP faults along the North African margins and along the Balearic margin accommodate the westward migration of the Gibraltar slab (e.g., Spakman & Wortel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The North African plate overrides the Alboran domain leading to the present‐day surface expression of the STEP fault (Alboran Ridge, Yusuf fault, and Jebha and Nekor faults) that does not coincide with the present‐day deep structure (Figure 14d). The actual boundaries of the slab tear are determined by mapping the missing orogenic root under the Betics and Rif (e.g., Mancilla et al, 2015; Hidas et al, 2019). The convergence motion is oblique to the E‐W striking folds and major conjugate fault sets causing the reactivation and rotation of the Miocene SAR‐Alboran Ridge and Yusuf fault (Figure 14d).…”
Section: Discussionmentioning
confidence: 99%
“…While solid line is the fit line using a Zener parameter of 0.52 adopted from Tasaka et al (2014). The background of the figure is modified after Hidas et al (2019).…”
Section: Discussionmentioning
confidence: 99%